Investigation of extracellular L-citrulline concentration in the striatum during alcohol withdrawal in rats - (:unkn) unknown (KLUWER ACADEMIC/PLENUM PUBL, 2001)
In this study, changes in striatal extracellular L-citrulline concentrations were investigated hourly for 5 h following alcohol withdrawal in chronic alcohol feeding Wistar rats. Alcohol (7.2% ethyl alcohol, v/v) was given to rats as modified liquid diet for 20 days. Signs of alcohol withdrawal appeared from the 1st h of alcohol withdrawal and the total alcohol withdrawal scores remained higher during the course of experiments. The mean of basal levels of L-citrulline in the microdialysis samples collected in conscious rat model from the striatum of control and alcoholized rats were found to be 1.28 +/- 0.48 muM and 0.35 +/- 0.08 muM, respectively. L-citrulline levels in the striatum of alcoholized rats increased by 4 folds significantly within I h following alcohol withdrawal. The increased striatal L-citrulline concentration was blocked by N-G-nitro-L-arginine methyl ester (L-NAME; 60 mg/kg), a nitric oxide synthase inhibitor, pretreatment. Our results indicate an increased L-citrulline level in the rat striatum during early alcohol withdrawal and this situation may be related to an increased nitric oxide production.
Keywords: alcohol withdrawal; rat striatum; microdialysis; L-citrulline; L-NAME; nitric oxide; NITRIC-OXIDE SYNTHESIS; ETHANOL WITHDRAWAL; CLASSICAL TRANSMITTERS; RECEPTOR DENSITY; IN-VIVO; INHIBITION; SYNTHASE; BRAIN; ARGININE; GLUTAMATE